دراسة تحليلية لتجارب دول ناجحة في تنمية صادراتها وإمكانية الاستفادة منها في سورية - عثمان, سلمان; صقر, محمد; علي, علاء (Latakia University Journal - Economic and Legal Sciences Series, 2014)
أصبحت قضية التصدير تشكل المحور الأساسي في رسم السياسات الاقتصادية للدول، على اعتبار أن الصادرات محركاً هاماً في عملية النمو الاقتصادي،لذا تسعى الدول جادةً لتنمية صادراتها وتحسين قدرتها التصديريةمن خلال تبني إستراتيجية تنمية الصادرات. هناك العديد من التجارب الدولية في هذا المجال والتي حققت نجاحاً ملحوظاً في تحسين أدائها التصديري ورفع مستوى أدائها الاقتصادي. عند دراسة واقع الصادرات السورية تبين أنها تعاني من عدة نقاط ضعف تنعكس سلباً على واقع الاقتصاد السوري ، لذا يهدف البحث لمعالجة تلك النقاط بالاعتماد على إستراتيجية تنمية الصادرات المطبقة في دول مختلفةمن العالم باعتبارها تمثل سياسة تنموية مهمة ووسيلة لدفع عجلة النمو الاقتصادي، كما يهدف إلىإمكانية الاستفادة من تلك التجارب الناجحة في صياغة إستراتيجية وطنية هادفة لتنمية الصادرات السورية بهدف تحسين موقعها في الأسواق الخارجية وتحقيق معدلات نمو مستقرة ومرتفعة. The issue of export has become a main focus of economic policy-making states, given that exports are an important engine in the process of economic growth. So countries seriously seek to develop their exports and improve the export capacity through the adoption of an export development strategy. There are many international experiences in this field, which have achieved remarkable success in improving their export performance and raising the level of their economic performance. When studying the reality of Syrian exports, it is evident that they suffer from several weaknesses negatively reflected on the reality of the Syrian economy. This research aims to address those points, depending on the strategy of developing exports applied in different countries of the world, representing an important developmental policy and a means for boosting economic growth. It also aims to highlight the possibility of benefiting from successful experiences by formulating a national strategy for the development of Syrian exports in order to improve their position at foreign markets and achieve stable and high growth rates.